Predictores de vasoespasmo cerebral sintomático en la hemorragia subaracnoidea espontánea - Ezequiel López Espinosa; Miguel Ángel Serra Valdés; Maira Sarmiento Matamoros (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Background: subarachnoid hemorrhage accounts for only 2 to 5 % of all cerebrovascular diseases; however it causes approximately 25 % of all deaths related to them. Objective: to identify the factors contributing to the prediction of symptomatic cerebral vasospasm in patients diagnosed with subarachnoid hemorrhage. Methods: a prospective longitudinal study was conducted in 73 patients aged 15 years or more with subarachnoid hemorrhage admitted to the Carlos Manuel de Céspedes Provincial General Hospital in Granma province from January 2010 through October 2011. Descriptive and inferential statistics in addition to clinical epidemiology resources were used. Results: among the patients studied, 15 developed symptomatic cerebral vasospasm (20.5 %). Closely-related factors included: advanced age, loss of consciousness at the time of onset, intracranial hypertension as major clinical syndrome, water-electrolyte imbalance and respiratory arrhythmias. Low scores on the Glasgow Coma scale and high scores on the Hunt and Hess scale and the World Federation of Neurosurgical Societies scale are related to the presence of symptomatic cerebral vasospasm in spontaneous subarachnoid hemorrhage. Conclusions: in most cases, diagnosis of vasospasm after subarachnoid hemorrhage is clinically established. Relying on clinical predictors can be useful.